Improvement on the mechanical properties of boron suboxide (B60) based composites using other compounds as second phase - Johnson, Oluwagbenga Temidayo (My University, 2009)
The problem of low fracture toughness and the difficulties to densify has delayed the application of B6O materials as superhard materials in the industry. Therefore, in this work, effort has been directed towards improving the fracture toughness and densification of these materials by incorporating suitable secondary phases and tailoring the microstructure to the desired properties. Boron suboxide (B6O) powder was synthesized from the reaction of amorphous boron and boric acid powders. The synthesized B6O powder was hot pressed at 1900oC and 50MPa. In addition to the pure B6O material, composites with transition metals, transition metal oxides, transition metal borides and rare-earth metal oxides were prepared at 1850oC. The microstructure, phase composition and properties of resulting materials were investigated. A boride secondary phase was formed after sintering. Materials with densities higher than 95% theoretical density were achieved for the composites. Although the pure B6O sample was brittle, fracture toughness of 7.6±1.1 MPam0.5 was obtained for the B6O+FeB composite. This study gives a basis for optimizing the sintering additives with potentials for improving the hardness and fracture toughness of B6O materials.